UV-Vis characterization of diamond-like carbon thin films deposited using (DC-PECVD) /cNur Alifah Ab. Rahman - Nur Alifah Ab. Rahman, 1982-; Bakar Ismail, supervisor; Fakulti Sains (2010)
Thesis (Sarjana Sains (Fizik)) - Universiti Teknologi Malaysia, 2010